An assessment of public knowledge, perception and acceptance of nuclear energy in Ghana. (1st October 2020) - Odonkor, Stephen T.; Adams, Samuel
Abstract: Social acceptance of nuclear energy is critical for its successful implementation. Ghana has decided to develop nuclear energy to augment its growing demand for electricity. The study assesses the level of public knowledge, perceptions, risk and policy support for nuclear power development among Ghanaians. A nationally representative survey of Ghanaian adults (N = 1128), aged 18 and older, was conducted from August 1 to 2018 to November 28, 2018. The findings of the study indicate that, 72% of respondents have knowledge of nuclear energy, however only 28% of the respondents were aware of Ghana's nuclear development plan. We observed that about 51% of the respondents support Ghana's nuclear development plan despite the low level of awareness. Most respondents showed concern for the safety and prospects of having nuclear energy, fully adopted in the country. Social risk investment was identified as the most significant risk associated with nuclear power development. Majority of the respondents were much more 'interested' in how nuclear energy will impact or affect people or communities should they adopt the technology or in case of accidents. These findings provide useful insights for nuclear energy adoption and policy directions in Ghana. The Government of Ghana and other major stakeholders of nuclear power technology should develop a communication strategy to increase and sustain publicity and education of Ghana's nuclear power development plan to citizens.